Organizational Culture and Job Satisfaction: The Dark Side of Organizational Politics - Tommy Vara Berlin; Ririn Handayani; Fahmi Oemar (Yayasan Education Al Aqsho Modern, 2022)
This study aims to see how organizational culture affects job satisfaction at the Pekanbaru Police Satreskrim. In addition, this study will also look at the interaction of the two variables, how organizational politics mediates the influence of organizational culture on job satisfaction. This type of research is explanatory research. The population is members of the Pekanbaru City Police, totaling 95 people. Data analysis in this study used SEM-PLS. Based on the data processing, it was found that there are habits that have become a culture in the Pekanbaru City Police which will determine the good or bad perceptions of its personnel on political behavior in the organization. In addition, the understanding of the political behavior of its personnel is influenced by the culture adopted by the Pekanbaru Police. The limitation of this study is the lack of population size used. So it is suggested to further researchers to examine the organizational culture of Hofstede (1984) per indicator. So that it can explain in more detail the influence of each cultural indicator on organizational politics and job satisfaction.